(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research is based on the CDA theory and its analytical methods advocated by Thomas N. Huckin. While the discussion used a descriptive qualitative research method, dealing with data in terms of words rather than statistics, trying to arrive at a detailed description of something systematic. It begins by analyzing some features of the text as a whole. Subsequently, some features are analyzed at sentence and word level. Since it is a critical discourse, these features are analyzed critically. In fact, the flaw is found in analyzing each of the characteristics of Michelle Obama’s speech. The last makes a contextual interpretation, summarizing how the language, power and ideology is used in Michelle Obama’s speech. The interpretation is also based on the results of the two previous analyses. The end result indicates that CDA can discover the relationships among language, power, and ideology. Through the language used, it is able to be regarded as the power of energy and the cause of the speaker, in which the power is strongly felt and the ideology is honestly visible in addition to understandable.